Correlations between Modic change and degeneration in 3-joint complex of the lower lumbar spine: A retrospective study. Issue 38 (September 2018) - Guo, Runsheng; Yang, Xiaowei; Zhong, Yanchun; Lai, Qi; Gao, Tian; Lai, Fuchong; Dai, Min; Zhan, Ping; Zhang, Bin
Abstract: Background: Modic changes (MCs) associated with low back pain (LBP) have been assessed in a few studies. It has been documented that patients with LBP have MCs in a specific segment, but the relationship between facet joint or disc degeneration and MCs is still disputed. Thus, we aimed to evaluate the correlation between MC and facet joint or disc degeneration using imaging. Methods: Imaging data of patients were retrospectively analyzed at the Orthopedic Department of the First Affiliated Hospital of Nanchang from January 2014 to August 2017. MCs, facet joint degeneration, and disc degeneration in L3-S1 were evaluated by lumbar MRI. χ 2 test and contingency correlation coefficient were used for the statistical analyses, and a P value < .05 was considered statistically significant. Results: In the descriptive statistical analysis, MCs were found to have the highest incidence in the L4–5 segment. Type II MCs had a higher incidence than type I and type III MCs regardless of whether they were in the L3–4, L4–5, or L5-S1 segment. On one hand, MCs were more frequently distributed in grades 3, 4, and 5 of the degenerative lumbar discs regardless of whether they were in the L3–4, L4–5, or L5-S1 segment ( P < .000, V: contingency coefficient >0); particularly, type II MCs were closely related to lumbar disc degeneration ( P < .05, V > 0). On the other hand, MCs were more frequently distributed in grades 1, 2, and 3 of the degenerative lumbar facet regardless of whether they were in the L3–4, L4–5, or L5-S1 segment ( P < .05, V > 0). Particularly, type II MCs were frequently distributed in grades 1, 2, and 3 of the facet joint in the L4–5 and L5-S1 segments ( P < .05, V > 0). Conclusion: MCs are correlated with the grade of lumbar spine degeneration, including lumbar disc and facet joint degeneration. MCs, especially type II, frequently occurred in severe degeneration of the lumbar disc and facet joint. Thus, MC may be one of the manifestations of lumbar disc and facet joint degeneration.